2023
DOI: 10.1038/s41545-023-00232-2
|View full text |Cite
|
Sign up to set email alerts
|

Potential benefits of public–private partnerships to improve the efficiency of urban wastewater treatment

Abstract: For emerging economies lacking public budgets, continuous improvement of urban wastewater treatment efficiency (UWTE) requires effective government supervision of wastewater treatment infrastructures (WTIs) and participation of private capital seeking to profit-maximising. However, to what extent this public–private partnership (PPP) model, aimed at a reasonable sharing of benefit and risk, in delivering WTIs can improve the UWTE is unknown. We evaluated the impact of the PPP model on the UWTE by collecting da… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…The chain‐wide effects on water, nitrogen, phosphorus, and biomass (HANPP) consumption exhibit a significant degree of heterogeneity due to regional differences in dietary composition. In order to determine the effects of the various sectors (Cheng et al., 2024; Meng et al., 2021; Ogunmoroti et al., 2022) and create suitable policy suggestions (Cheng et al., 2023; Tahir et al., 2022), this calls for the construction of more accurate input‐output tables. Therefore, further consideration will also be given to this in the future, as data allows.…”
Section: Discussionmentioning
confidence: 99%
“…The chain‐wide effects on water, nitrogen, phosphorus, and biomass (HANPP) consumption exhibit a significant degree of heterogeneity due to regional differences in dietary composition. In order to determine the effects of the various sectors (Cheng et al., 2024; Meng et al., 2021; Ogunmoroti et al., 2022) and create suitable policy suggestions (Cheng et al., 2023; Tahir et al., 2022), this calls for the construction of more accurate input‐output tables. Therefore, further consideration will also be given to this in the future, as data allows.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is not clear to what extent this PPP model, which aims to reasonably share the benefits and risks of WTI delivery, can improve UWTE. Cheng et al (2023) evaluated the impact of the PPP model on UWTE, the author collected data from 1303 urban wastewater treatment PPP projects in 283 prefecture-level cities in China from 2014 to 2019 using data coverage analysis and a Tobit regression model. The UWTE was significantly higher in prefecture-level cities that implemented a PPP model in the construction and operation of WTI, especially in cities with feasibility gap subsidies, competitive procurement, privatized operations, and non-demonstration.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Reasons for establishing a compensation mechanism for PPP projects [20,[35][36][37] Compensation link between construction period and operation period of PPP projects [38,39] The importance of the compensation mechanism during the operation period of PPP projects [40,41] Recyclingremanufacturing two-stage performance Performance management theory [42] Performance evaluation of PPP project operation period [43][44][45] Two-stage performance research of recycling and remanufacturing [25,46,47]…”
Section: Cdw Recycling Ppp Projectsmentioning
confidence: 99%
“…For this reason, in the current research, more scholars have focused on the direction of compensation during the construction period. Relevant scholars have successively confirmed that compensation during the construction period by the government has a significant role in promoting the success rate of project operations and social benefits [38]. At the same time, they calculated and adjusted the amount of government compensation during the construction period [39].…”
Section: Compensation Mechanism During the Ppp Projects Operation Periodmentioning
confidence: 99%